(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Nouns, one of the essential parts of speech, serve as the backbone of language, providing names for people, places, things, ideas, and phenomena. Their grammatical categories, including number, case, gender, and definiteness, enable nouns to adapt to the structural and semantic needs of a sentence. This article examines the definition, classification, and grammatical categories of nouns, highlighting their importance in syntax and semantics. Number: Highlights singular and plural forms. Case: Explains relationships between nouns and other sentence elements. Definiteness: Differentiates specific and nonspecific references. Cross-Linguistic Variation: Compares grammatical categories in English with other languages.